Scientific Approach-Based Fikih Learning Model - Sapiudin, Sapiudin (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractThis study aims to find a model of Fikih learning based on a scientific approach in Islamic Senior High Schools. The methodology used is qualitative analysis supported by quantitative data. This type of research uses the Research & Development (R & D)  approach. The source of the data is the Fikih learning based on the scientific approach held by MAN Insan Cendekia Serpong and MAN Insan Cendekia Gorontalo. The model that has been conceptualized is experimented on in MAN 1, South Tangerang City. The design of the scientific approach emphasizes the performance and exploration of students both independently and in groups.  research results show that scientific approach based learning can encourage students to be active and creative. Students are able to produce a useful product. So it can be concluded that the application of the intended model is considered effective in achieving learning objectives through the application of flexible and conditional steps 5 M. As a recommendation, this learning model innovation based on student-centric is considered feasible to be applied at various levels of education those are equal.AbstrakPenelitian ini bertujuan menemukan sebuah model pembelajaran Fikih berbasis pendekatan ilmiah di Madrasah Aliyah. Metodologi yang digunakan adalah analisis  kualitatif  yang didukung oleh data kuantitatif.  Jenis penelitian menggunakan pendekatan penelitian Research & Development (R&D). Sumber data adalah pembelajaran Fikih berbasis pendekatan saintifik yang diselenggarakan oleh MAN Insan Cendekia Serpong dan MAN Insan Cendekia Gorontalo. Model yang telah terkonsep di eksperimenkan di MAN 1 Kota Tangerang Selatan.  Desain pendekatan ilmiah ditekankan kepada kinerja dan eksplorasi siswa baik secara mandiri maupun kelompok. Diperoleh hasil penelitian, pembelajaran berbasis pendekatan ilmiah mampu mendorong siswa bersikap aktif dan kreatif. Siswa  mamapu menghasilkan suatu produk yang bermanfaat. Sehingga dapat disimpulkan bahwa penerapan model  dimaksud dinilai efektif untuk  mencapai tujuan pembelajaran melalui penerapan langkah  5 M yang fleksibel dan kondisional.  Sebagai rekumendasi, inovasi model pembelajaran  yang berbasis student centris ini dinilai layak untuk  diterapkan di berbagai  jenjang pendidikan yang  sederajat.  How to Cite: Sapiudin. (2019).   Scientific Approach-Based Fikih Learning Model. TARBIYA: Journal of Education in Muslim Society, 6(2), 155-168. doi:10.15408/tjems.v6i2. 14884.